Beyond Food Provision: A Critical Policy Analysis of Indonesia’s Free Nutritious Meal Program - Suryani Jihad; A. Rellang; Musafir (CV Kalimasada Group, 2026)
This study aims to critically analyse the implementation of Indonesia’s Free Nutritious Meal Program as a public service policy in improving student outcomes, with a focus on governance, socio-economic implications, and educational integration. Employing a qualitative approach with policy analysis, the study utilizes document analysis of government reports, academic literature, and relevant secondary data. The findings reveal that while the program demonstrates strong potential in supporting nutritional intake and enhancing learning readiness, its effectiveness is constrained by several challenges. These include limitations in transparency and stakeholder participation, uneven involvement of local economic actors, and inconsistencies in service quality, particularly regarding food acceptability and safety. Moreover, the program remains largely disconnected from the educational process, unlike more integrated approaches such as Shokuiku. The study concludes that a more inclusive, transparent, and education-oriented policy design is necessary to maximize the program’s impact on sustainable human capital development.